(untitled) (TEJUELO. Didáctica de la Lengua y la Literatura. Educación, 2022)
Este estudio pretende definir el concepto de educación que tiene el futuro profesorado de Educación Infantil y Primaria de la Universidad de Cádiz a través de una prueba de léxico disponible según la formación académica recibida. Se aborda desde un enfoque mixto para constatar las diferencias léxicas tomando como referencia las variables ‘grado’ y ‘curso’. Han participado 613 alumnos del Grado en Educación Infantil (n= 323) y en Educación Primaria (n= 290) durante el curso 2018/2019, los cuales hicieron pruebas de léxico disponible en español, inglés y francés. Los resultados reflejan una educación ligada a: respeto, pública, valores, escuela, alumno, niño… Las pruebas ANOVA factorial intersujeto revelaron que no se producen interacciones en ningún idioma entre las variables dependientes ‘curso x grado’. Sin embargo, se observan los efectos principales de la variable ‘curso’, en español, y ‘curso’ y ‘grado’, en inglés. En francés tan solo es significativo el ‘grado’. Esto nos lleva a concluir que el léxico disponible de los informantes en español aumenta conforme lo hace su formación académica. No obstante, en ambas lenguas extranjeras incide el grado, destacando en productividad los informantes de Educación Primaria frente a los de Educación Infantil. Abstract This study aims to define the concept of education that the future teachers of Early Childhood and Primary Education of the University of Cádiz have through a lexical availability test according to their academic training. It is approached from a mixed approach to verify the lexical differences taking as a reference the variables ‘degree’ and ‘course’. 613 students of the Degree in Early Childhood Education (n = 323) and Primary Education (n = 290) have participated during the 2018/2019 academic year, who took lexical availability tests in Spanish, English, and French. The results reflect an education linked to respect, public, values, school, student, child… The inter-subjects effects of factorial ANOVA revealed that there are no interactions in any language between the dependent variables ‘year x degree’. However, the main effects of the variable ‘course’, in Spanish, and ‘course’ and ‘degree’, in English, are observed. In French, only the ‘degree’ is significant. This leads us to conclude that the lexicon available to informants in Spanish increases as their academic training increases. However, in both foreign languages the ‘degree’ has an impact, highlighting in productivity the informants from Primary Education compared to those from Early Childhood Education. Keywords: lexical availability; education; initial teacher training; lexicostatistics; bilingualism.